2004
DOI: 10.5194/angeo-22-3073-2004
|View full text |Cite
|
Sign up to set email alerts
|

Large aerosol optical depths observed at an urban location in southern India associated with rain-deficit summer monsoon season

Abstract: Abstract. Aerosol spectral optical depth (AOD) measurements were made covering three years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…However, several satellite-based observations have demonstrated that the aerosol distribution over the Arabian Sea and Indian Ocean are significantly influenced by the transport of dust aerosols from the Arabian Desert (Husar et al, 1997;Li and Ramanathan, 2002;Rajeev et al, 2004). Two channel inversion of Mishchenko et al (1999) showed that the Angstrom exponent is very nearly uniform over the Arabian Sea, Bay of Bengal and the tropical Indian Ocean and has a mean value of ∼0.4 during the summer monsoon period, which is grossly in agreement with the Angstrom exponent observed at Bahrain Dubovik et al, 2002), the Indian Ocean island of Kaashidhoo ) and the ship-borne observations at the Arabian Sea (Vinoj and Satheesh, 2003). showed that the dust aerosols are less absorbing and have a mean single scattering albedo of 0.97 in the visible region.…”
Section: Data and Methods Of Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…However, several satellite-based observations have demonstrated that the aerosol distribution over the Arabian Sea and Indian Ocean are significantly influenced by the transport of dust aerosols from the Arabian Desert (Husar et al, 1997;Li and Ramanathan, 2002;Rajeev et al, 2004). Two channel inversion of Mishchenko et al (1999) showed that the Angstrom exponent is very nearly uniform over the Arabian Sea, Bay of Bengal and the tropical Indian Ocean and has a mean value of ∼0.4 during the summer monsoon period, which is grossly in agreement with the Angstrom exponent observed at Bahrain Dubovik et al, 2002), the Indian Ocean island of Kaashidhoo ) and the ship-borne observations at the Arabian Sea (Vinoj and Satheesh, 2003). showed that the dust aerosols are less absorbing and have a mean single scattering albedo of 0.97 in the visible region.…”
Section: Data and Methods Of Analysissupporting
confidence: 84%
“…The latitude gradient in the two BoB sectors is very small during September and October (nearly zero in EBoB sector). The gradient in all five sectors show a peak during the March-April period when the AOD value over the Indian continent shows also a maximum (Moorthy et al, 1993;Vinoj et al, 2004). A sharp increase in gradient is observed in the Arabian Sea sectors during the July-August period while this feature is totally absent in the BoB sectors.…”
Section: Latitude Variation Of Aodmentioning
confidence: 96%
“…The high and low values of AOD were found to be 1.12 and 0.38 in April and August respectively. The maximum value of AOD in April at 500 nm in Bangalore is 0.5 [17]. Increasing aerosol input in April causes to increase aerosol optical depth.…”
Section: Monthly Variations Of Aodmentioning
confidence: 95%
“…Due to larger variations in light scattering caused by changes in fine-mode aerosols (Schuster et al, 2006), the monthly variability of AOD 440 is more intense than that at 936 nm, ranging from as low as ~0.3 (March 2010) to as high as ~1.4 (November 2012). More or less similar pattern of the spectral AOD variation has been found over Delhi (Lodhi et al, 2013), Hyderabad (Sinha et al, 2012), Ahmedabad (Ganguly et al, 2006), Dibrugarh (Gogoi et al, 2009), Kullu valley (Guleria et al, 2011), Varanasi (Tiwari and Singh, 2013), Pune (Dani et al, 2012), Bangalore (Vinoj et al, 2004), among many others.…”
Section: Severe Aerosol Loading Over Greater Noidamentioning
confidence: 95%